THE ROLE OF SOCIAL NETWORKING ON POLITICAL CONSIOUSNESS OF UNIVERSITY STUDENTS IN LOWER NORTHEASTERN REGION, THAILAND - Nalinee Thongprasert (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2014)
This research aims to investigate the behavior of social networking in receiving political information and involving in politics of the university students in lower northeastern region and to examine the relationship of the reflection after receiving information through the social networking and the democratic and power-oriented consciousness of the respondents. The effect of the political consciousness on political involvement and monitoring of politician’s work through the social networking are also the focus of the study. The research used a mixed-method of quantitative and qualitative approaches. A focus group was employed in the qualitative data collection from which 21 samples including chairman of the student were selected. The qualitative collected data were analyzed in order to that the results could be used to base the survey questionnaire. The questionnaire was then utilized to collect the quantitative data from 427 sampled students in eight universities. The statistics including frequency, percentage, mean, standard deviation, Pearson’s product moment correlation, and multiple regressions analysis were employed in data analysis. Receiving political information three to four times a week is found in mean frequency of the respondents. The behavior of the information recipients found not to voice their opinions and not to pass on the received information to other people on Facebook or other social networking is very close in proportion to those sharing their views and passing on the information to friends on the social networking. Only getting interested but not wanting to get involved in politics is the main reason of the samples. The reflection after receiving information results in most respondents saying they are able to understand, analyze, and identify facts of the received messages. And the ability in identifying of facts is related to the respondent’s democratic consciousness while the inability in identifying of facts is relevant to the power-orientation. Hypothesis test indicates the democratic consciousness having relationship with the positive effect of political involvement and monitoring of politician’s work whereas the power-oriented consciousness is found to be opposite in thatthe more the consciousness found to be power-oriented the less tendency to get involved in politics and monitoring of politician’s work of the respondents exists.